2023
DOI: 10.3390/systems11090464
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Maturity Model for Software Quality Assurance Practices

Ahmad Al MohamadSaleh,
Saeed Alzahrani

Abstract: The advancements in the technology landscape and software development in recent years mandate paying attention to Software Quality Assurance (SQA) because it is becoming significantly important and complex. SQA is a set of activities within the software development lifecycle that aims at reducing development and testing costs, improving the quality of the software systems, and increasing customer satisfaction. Thus, the objective of this paper is to build a SQA maturity model, particularly in the telecommunica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
(112 reference statements)
1
0
0
Order By: Relevance
“…In addition, the empirical results showed a positive association between IS maturity and IS quality. This result aligns with the idea that the level of maturity could influence IS quality in varying ways (Ragowsky et al 2012;Al MohamadSaleh and Alzahrani 2023). The authors of Voordijk et al (2003) found that the successful implementation of the ERPS depended on the strategic role of IT, IS maturity, firm strategies, and the implementation approach.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, the empirical results showed a positive association between IS maturity and IS quality. This result aligns with the idea that the level of maturity could influence IS quality in varying ways (Ragowsky et al 2012;Al MohamadSaleh and Alzahrani 2023). The authors of Voordijk et al (2003) found that the successful implementation of the ERPS depended on the strategic role of IT, IS maturity, firm strategies, and the implementation approach.…”
Section: Discussionsupporting
confidence: 81%